Visible-Light-Induced Oxidative Generation of o-Quinone Methides for Inverse-Electron-Demand [4+2] Cycloaddition Reactions - Nohara, Shoya; Iwai, Suguru; Yamaguchi, Naoya; Asada, Yosuke; Kamiyama, Yusuke; Tanaka, Yuta; Tanaka, Kenta; Hoshino, Yujiro (Synlett, 2023)
Organophotoredox-catalyzed oxidative generation of o-quinone methides (o-QMs) for inverse-electron-demand [4+2] cycloaddition reactions has been developed. One-electron oxidation of 2-(sulfanylmethyl)phenols by thioxanthylium photoredox catalyst generated o-QMs, which reacted with various styrenes to produce chromanes with high regioselectivity. This reaction offers a valuable approach for in situ generating o-QMs via one-electron oxidation process under irradiation with mild green light.
Keywords: o-quinone methide; photoredox; visible light; chromane; [4+2] cycloaddition